Strategies for Improving Phosphorus Use Efficiency in Lettuce Grown on Histosols - Gustavo Kreutz; Jehangir Bhadha; Guodong Liu; Marcio Resende; Alan Wright; D. Calvin Odero; German Sandoya (EDIS)
The global demand for P fertilizers has been significantly increasing, resulting in higher costs and environmental concerns associated with eutrophication. Fertilizer expenses and environmental risks can be reduced through the implementation of sustainable strategies. This new 6-page publication of the UF/IFAS Horticultural Sciences Department compiles several strategies to improve the utilization of P fertilization in lettuce grown in the Everglades Agricultural Area. https://edis.ifas.ufl.edu/hs1423